2011
DOI: 10.2478/v10214-011-0001-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the activation energy of viscous flow for hen egg-white lysozyme obtained on the basis of different models of viscosity for glass-forming liquids

Abstract: The paper presents the results of viscosity determinations on aqueous solutions of hen egg-white lysozyme at a wide range of concentrations and at temperatures ranging from 5 o C to 55 o C. On the basis of these measurements and different models of viscosity for glass-forming liquids, the activation energy of viscous flow for solutions and the studied protein, at different temperatures, was calculated. The analysis of the results obtained shows that the activation energy monotonically decreases with increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…The measurements have shown the batch-and species-independence; the bovine and human Fg preparations gave very similar results. The extracted value of activation energy for Fg self-diffusion, E d = 21.3 kJ/mol in 1.42 mg/mL Fg solution, agrees well with 18.0−20.4 kJ/mol determined earlier for water in a protein (lysozyme) solution 36 at the equivalent protein concentrations. For comparison, the activation energy for self-diffusion of pure water is E W = 17.8 kJ/mol.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurements have shown the batch-and species-independence; the bovine and human Fg preparations gave very similar results. The extracted value of activation energy for Fg self-diffusion, E d = 21.3 kJ/mol in 1.42 mg/mL Fg solution, agrees well with 18.0−20.4 kJ/mol determined earlier for water in a protein (lysozyme) solution 36 at the equivalent protein concentrations. For comparison, the activation energy for self-diffusion of pure water is E W = 17.8 kJ/mol.…”
Section: ■ Resultsmentioning
confidence: 99%
“…In the Rouse model (iii), the beads roughly represent the distal and central globular parts connected by the coiled-coils. In our previous study of the Fg molecule in solution, we showed that the coiled-coil connectors behave as entropic springs. ,, In the Rouse model, each bead is characterized by its own friction (see eq ), and water molecules drain freely through a moving protein chain. Because the Rouse model ignores hydrodynamic interactions of a biopolymer chain with solvent and neglects the intrinsic viscosity [ η ], a disagreement between the model predictions and the crystal structure would imply the importance of hydrodynamic coupling.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…This equation gives the functional dependence of the viscosity on temperature and can be used for obtaining the functional dependence of the activation energy of viscous flow on temperature. After inserting the equation (1) into the definition (3), differentiation and simple transformations we obtain the following expression for the activation energy of the solution (Monkos, 2011a):…”
Section: Avramov' S Modelmentioning
confidence: 99%
“…The numerical values of the parameters F s (c) and T o,s (c) , which are important in the further part of this work, for all measured concentrations of ovalbumin, are gathered in Table 1. As in the Avramov's model function from relation (6) can insert to the definition (3) and obtain the functional dependence of the activation energy of the solution (Monkos, 2011a):…”
Section: Free-volume Modelmentioning
confidence: 99%
See 1 more Smart Citation